A low-fidelity game-based approach to teaching basic health assessment: It’s not just a game! - Pottere, Danita; Tolson, Danita (International Journal of Advanced Nursing Studies, 2017)
Game-based teaching-learning activities positively influenced student learning in academic programs, particularly in nursing education where learning nursing concepts, disease processes, assessment skills and management may be overwhelming in the traditional classroom setting. The purpose of this paper was to describe a teaching—learning approach, and to discuss lessons learned to use games to teach basic health assessment in first-level BSN program. The approach and organization constructs were interventional, descriptive and non-experimental. In conclusion, lessons learned yield that teaching health assessment content as a game may promote student and faculty involvement, excitement, and motivation. A game checklist was developed based on feedback from students and faculty. The game led to the development of a guide for game-based approaches to teaching pre-clinical undergraduate nursing students health assessment content.